Implementasi Kebijakan Pengelolaan Anggaran Pendapatan Dan Belanja Desa (APBDES) Untuk Meningkatkan Pembangunan Dan Kesejahteraan Masyarakat (Studi Kasus di Desa Ngawen Kecamatan Muntilan Kabupaten Magelang) - Ilyas Febriyan; Dian Lestari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to analyze the implementation of APBDes policies in improving community development and welfare in Ngawen Village, Muntilan District, Magelang Regency. In implementing the APBDes policy, it is still dominated by the village government. APBDes management policies must apply the principles of Good Governance which include participation, transparency and accountability so that the goals in village development can be achieved and realized. The analysis technique used is descriptive qualitative analysis. Research data obtained through interviews, observation, and documentation. This research was analyzed by case study method. The results of the study show that Ngawen Village has not fully complied with the provisions of laws and regulations in financial management during the implementation of the APBDes. This requires synergy between the district and sub-district governments in terms of assisting and supervising the implementation of village finances.